Do you hear what I see? How do early blind individuals experience object motion?. (30th January 2023) - Fine, Ione; Park, Woon Ju
Abstract : One of the most important tasks for 3D vision is tracking the movement of objects in space. The ability of early blind individuals to understand motion in the environment from noisy and unreliable auditory information is an impressive example of cortical adaptation that is only just beginning to be understood. Here, we compare visual and auditory motion processing, and discuss the effect of early blindness on the perception of auditory motion. Blindness leads to cross-modal recruitment of the visual motion area hMT+ for auditory motion processing. Meanwhile, the planum temporale, associated with auditory motion in sighted individuals, shows reduced selectivity for auditory motion. We discuss how this dramatic shift in the cortical basis of motion processing might influence the perceptual experience of motion in early blind individuals. This article is part of a discussion meeting issue 'New approaches to 3D vision'.